The Effect of Legal Framework on the Delivery of Devolved Services in Selected Counties in Kenya - Karama , Fauziya Brek (American Journal of Social Sciences and Humanities, 2022)
Kenya devolution was found to be an ambitious program, counties are facing challenges in enhancing devolved service delivery .The main purpose of this study was to establish the effect of legal framework on devolved service delivery. The study targets a population of 35,444 staff from 8 counties. The study has adopted a mixed method approach.Structured and open-ended questionnaires were used in the study. Data analysis was done using descriptive statistics, correlation and regression analysis. More results revealed that legal framework had positive and significant on service delivery. Based on the findings the study concludes legal framework significantly improves service delivery. Thus, legal framework in county governments reinforces management support, financial resources and stakeholder engagement thus increasing the propensity to service delivery. Hence, at high levels of legal framework, the effect of management support, financial resources and stakeholder engagement and delivery of devolved services is stronger and significant as opposed to when it is at low or medium level.